2011
DOI: 10.1590/s1806-66902011000100028
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação citoquímica durante a germinação de sementes de sorgo envelhecidas artificialmente e osmocondicionadas, sob salinidade

Abstract: Palavras-chave -Sorgo-sementes. Citoquímica. Sementes-morfologia. Estresse salino.Abstract -The aim of this study was to evaluate the rate of water absorption and cytochemical changes in primed and aged seeds of sorghum during germination under absence or presence of 100 mM NaCl. The initial batch of seeds of sorghum cv. IPA-1011, was divided into two batches of different levels of vigor, by the accelerated aging of half seeds, with half of each batch also referred to the priming of polyethylene glycol 6000 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
2
6
0
1
Order By: Relevance
“…Disruption of ion balance and increased reactive oxygen species lead to cell integrity and homeostasis disruption; the latter acts on different chemical components of the seed, disrupting the metabolic cycle. All these conditions lead to loss of seed viability or reduced performance [19][20][21][22]. The study findings were similar to those of the previous studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Disruption of ion balance and increased reactive oxygen species lead to cell integrity and homeostasis disruption; the latter acts on different chemical components of the seed, disrupting the metabolic cycle. All these conditions lead to loss of seed viability or reduced performance [19][20][21][22]. The study findings were similar to those of the previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Enzyme activity is impaired, and metabolic activity is restricted. Increased reactive oxygen species disrupt cell integrity and homeostasis [20][21][22]. For these reasons, it is not possible to maintain production sustainably.…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (2008) verificaram que, em sementes de trigo, ocorre alteração nos constituintes celulares quando submetidas a estresse salino com NaCl. A toxidez causada pelo estresse salino em sementes de sorgo pode resultar em alterações morfológicas e citoquímicas (OLIVEIRA et al, 2011). De acordo com os resultados observados neste estudo, é possível que o KCl e o NaCl, sejam fitotóxicas para o repolho, e possam provocar alterações celulares e prejudiquem os processos fisiológicos da germinação e dos desenvolvimento de plântulas, destacadamente nas sementes do lote de baixa viabilidade.…”
Section: Salunclassified
“…Lopes et al (2013) also observed reduction of these protein bodies along the germination in seeds of Jatropha. The presence of XP stained globular protein bodies was also observed in seeds of Sorghum bicolor (OLIVEIRA et al, 2011) and Cereus jamacaru (ALENCAR et al, 2012).…”
Section: Resultsmentioning
confidence: 87%